The Impact of Directed Credit Policy on Bank Credit to the Private Sector in Ethiopia: Case of Government Bill Purchase Directive - Fekadu, Gardachew Worku (Archives of Business Research, 2018)
In April, 2011, National bank of Ethiopia (NBE) has introduced an explicit directive called 27% NBE Bill purchase directive that forces private banks to invest 27% of their every new loan disbursements in Governments securities for five years at a very low interest rate, 3%. The major theme of this study was to examine the effect of this directed credit policy on the Commercial banks’ credit to the private sector. The study used unbalanced panel data of eight years of eight banks for years from 2007 to 2014. The study finds that directed credit policy has negative but insignificant effect on the banks’ credit to the private sector. However capital and deposits were found to be significant determinants of private sector credit in Ethiopia. Thus the claim by private commercial banks, IMF and WB does not look strong and factual and hence it was conclude that the Bill purchase directive in Ethiopia does not have any significant crowding out effect on the private sector. Thus it would be recommended herewith that emphasis shall be given on capitalizing commercial banks. Moreover commercial banks shall introduce innovative and branchless channels for deposit mobilization for deposits were found to be the most significant determinants of private sector credit in Ethiopia.